THE INFLUENCE OF ORGANIZATIONAL CULTURE AND COMMUNICATION ON EMPLOYEE PERFORMANCE STUDIES ON BANK TABUNGAN NEGARA (PERSERO), TBK BANJARMASIN AND BANJARBARU AREAS, SOUTH KALIMANTAN - Adrian Rizky Pratama; Hastin Umi Anisah; Dahniar Dahniar (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
This study aims to determine and analyze the influence of organizational culture (X1) and communication (X2) as partially independent variables on employee performance (Y) as the dependent variable at Bank BTN Conventional and Syariah Banjarmasin & Banjarbaru areas. This research method uses a survey method approach by providing questionnaires to respondents. The population in this study were 184 people, while the sample in this study was conducted by using the Probabilty Sampling technique, namely by using Disproportionate Stratified Random Sampling with a total of 125 respondents. This type of research is a quantitative and explanatory research with multiple linear regression analysis techniques. The results of the study conclude that partially Organizational Culture has a significant effect on the Employee Performance of Bank BTN in Banjarmasin & Banjarbaru areas, South Kalimantan. The resulting influence shows a positive relationship to performance, that is, Organizational Culture is a habit that has been implemented in the Bank so that employee behavior / attitudes can coincide with one another. Other than that, Communication also has a significant effect on the Employee Performance of Bank BTN in the Banjarmasin & Banjarbaru areas, South Kalimantan. The resulting influence shows a positive relationship with performance. That is, Communication has an impact on performance. The communication that is established is very good and is as expected in coordination.